2014
DOI: 10.1007/s10534-014-9781-0
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of bacterial and viral biothreat agents on metallic copper surfaces

Abstract: In recent years several studies in laboratory settings and in hospital environments have demonstrated that surfaces of massive metallic copper have intrinsic antibacterial and antiviral properties. Microbes are rapidly inactivated by a quick, sharp shock known as contact killing. The underlying mechanism is not yet fully understood; however, in this process the cytoplasmic membrane is severely damaged. Pathogenic bacterial and viral high-consequence species able to evade the host immune system are among the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 36 publications
3
51
0
4
Order By: Relevance
“…ROS generated by the LED illumination may interact directly with unsaturated fatty acids in bacterial membranes and start lipid peroxidation, probably resulting in decreasing their membrane fluidity and then changing membrane components as well as disrupting membrane bound proteins [32]. Similar results were also obtained by Bleicher et al [29] who reported that the cytoplasmic membrane damage was observed in Yersinia pestis and Burkholderia strains by metallic copper surfaces due to oxidative damage.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…ROS generated by the LED illumination may interact directly with unsaturated fatty acids in bacterial membranes and start lipid peroxidation, probably resulting in decreasing their membrane fluidity and then changing membrane components as well as disrupting membrane bound proteins [32]. Similar results were also obtained by Bleicher et al [29] who reported that the cytoplasmic membrane damage was observed in Yersinia pestis and Burkholderia strains by metallic copper surfaces due to oxidative damage.…”
Section: Resultssupporting
confidence: 58%
“…The LIVE/DEAD staining of SYTO®9 and propidium iodide (PI) bound to nucleic acid is able to distinguish between damaged and intact bacterial membranes. Green fluorescing SYTO®9 (485/500 nm) penetrates the cytoplasmic membranes of both intact and damaged cells due to low molecular weight (~10 Da), while red fluorescing PI (490/635 nm) of higher molecular weight (668 Da) is only able to enter the damaged cytoplasmic membranes, resulting in a reduction in the intensity of SYTO®9 when two stains coexist within the cell [29][30][31]. In this study, healthy and non-illuminated cells exposed to 10°C for 7.5 h revealed green fluorescent signal of SYTO®9, whereas some LED-illuminated cells showed red fluorescence (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…9,[23][24][25] On the other hand, differences in killing rates due to different bacterial strains are comparatively smaller: >10 7 cfu of five different bacterial biothreat agents were all killed in 0.5-5 min on copper in dry plating experiments. 28 Similarly, >10 7 cfu of five clinical isolates of methicillin-resistant bacteria were killed in 60-270 min, and in another study, >99% of ten clinical isolates were all killed in 2 h in wet plating on copper. 29,30 We here chose E. coli as the model organism because it has been used in many fundamental studies on contact killing.…”
Section: A Contact Killing By Coppermentioning
confidence: 87%
“…In addition, the inactivation of monkeypox and vaccinia viruses have also been demonstrated on copper surfaces (Bleichert et al 2014).…”
Section: Copper As An Antiviral Surface Agentmentioning
confidence: 99%